2(x - 1) + 3 = x - 3(x + 1)
2x - 2 + 3 = x - 3x - 3
2x + 1 = - 2x - 3
2x + 1 = - 2x - 3 + 2x
4x + 1 = - 3
4x = 1 - 1 = - 3 - 1
4X = - 4
4x / 4 = - 4 / 4
x = - 1
- - - - - - - - - -s-
2007-01-20 07:15:10
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
2(x-1)+3=x-3(x+1)?
Perhaps it is required to solve this equation. Then :
2x - 2 + 3 = x - 3x - 3 or
2x - x + 3x = -3 + 2 - 3 or
4x = - 4 which leads to
x = -1. Answer.
Verified the answer. Ok
2007-01-20 06:33:34
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2(x - 1) + 3 = x - 3(x + 1)
2x - 2 + 3 = x - 3x - 3
2x + 1 = -2x - 3 (Add 2x and subtract 1 from both sides)
4x = -4 (Divide both sides by 4)
x = -1
Check:
2(-1 - 1) + 3 = -1 - 3(-1 + 1)
2(-2) + 3 = -1 - 3(0)
-4 + 3 = -1 - 0
-1 = -1
QED
2007-01-20 07:11:42
·
answer #3
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
2x-2+3 = x-3x-3
>> 2x+1 = -2x-3
>> 4x = -4
>> x= -1
2007-01-20 06:29:38
·
answer #4
·
answered by answerQuest 2
·
0⤊
0⤋
2(x-1)+3=x-3(x+1)
2x-2+3=x-3x-3
2x+1= -2x-3
+2x +2x
4x+1= -3
-1 -1
4x/4= -4/4
x= -1
There you go!
2007-01-20 06:34:16
·
answer #5
·
answered by Jaybond 2
·
0⤊
0⤋
2x - 2 + 3 = x - 3x -3
2x + 1 = -2x -3
2x + 2x = -3 -1
4x = -4
x = -1
Solution: {there is x in R | x = -1}
2007-01-20 07:43:05
·
answer #6
·
answered by aeiou 7
·
0⤊
0⤋
2x-2+3=x-3x-3=
2x+1=-2x-3=
2x+1-1=2x-3-1=
2x +2x=-2x-4 +2x=
4x=-4
x=-1
2007-01-20 07:51:52
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
2x -2 +3 = x-3x-3
2x +1 = -2x -3
4x = -4
x = -1
How's that for a 50+ old guy?
2007-01-20 06:36:54
·
answer #8
·
answered by Papa John 6
·
0⤊
0⤋
2x-2+3=x-3x+3
2x+1=-2x+3
4x=2
x=1/2
2007-01-20 06:46:12
·
answer #9
·
answered by verner66 2
·
0⤊
1⤋